"Every Little Furrow of Her Brow Makes Me Want To Stop": An Interpretative Phenomenologic Analysis of Mothers' Experiences With Juvenile Idiopathic Arthritis Treatments. Issue 11 (22nd July 2022) - Brandelli, Yvonne N.; Tutelman, Perri R.; Chambers, Christine T.; Parker, Jennifer A.; Stinson, Jennifer N.; Huber, Adam M.; Stirling Cameron, Emma; Wilson, Jennifer P.
Abstract : Objective: Children with juvenile idiopathic arthritis (JIA) are faced with a complex medical journey requiring consistent adherence to treatments to achieve disease management. Parents are intimately involved in JIA treatments; however, little is known about their experiences in this role. This is relevant as many treatments necessitate procedural pain (e.g., self‐injections) or side effects (e.g., nausea), which may impact a parents' ability to follow treatment plans. The objective of this study was to explore the lived experiences of parents who identified challenges with their child's JIA treatments. Methods: Parents of children with JIA who identified challenges with their child's treatments were invited to take part in semistructured interviews. Data were analyzed using interpretative phenomenological analysis. Results: Ten mothers of children with JIA (60% female with a mean age of 11.83 years [range 4–16 years]) participated. Four superordinate themes were present in mothers' experiences: 1) treatments altered mothers' roles within the family, increasing their caregiver burden and advocacy; 2) treatments positively and negatively impacted their relationships (e.g., increased support from others, decreased time with others); 3) treatments elicited various emotional responses (e.g., frustration, grief), which affected their well‐being; and 4) treatments were at times a source of internal conflict, affecting mothers' actions and adherence. Conclusion: Mothers' experiences with their child's JIA treatments affects them in various ways that can subsequently impact treatment adherence. Results highlight the value of supporting parents through these complex treatment regimens and incorporating their experiences in treatment decisions to help promote optimal outcomes for children with JIA and their families.